Goals and values of farmers revisited: Gasson fifty years on - Hill, Berkeley; Bradley, Dylan (Journal of Agricultural Economics, 2024)
Fifty years have passed since the Journal of Agricultural Economics published an article by Ruth Gasson on the goals and values of farmers in England. Gasson's research demonstrated the complexity of motives and, in particular, the importance farmers attached to the activities of farming (their intrinsic orientation), even among the operators of larger farms. Gasson's article has been widely cited as seminal by subsequent researchers on farmer behaviour. Governments have acknowledged the importance of understanding the motives of farm decision-makers when explaining their responses to economic and policy signals and designing schemes to shape farmers' behaviour. Brexit and the creation of national agricultural policies for each constituent UK country have highlighted the need for this better understanding, though precisely how this information can be used remains difficult. The continued dominance of an intrinsic orientation is particularly important for policies encouraging retirement and for the agri-environment. Gasson's legacy is also important in the quantification of goals and values to segment, and hence model, the heterogeneity of likely farmer responses to market and policy signals.
Keywords: Agricultural Policy; Farmers' Goals and Values; UK; Farm Management